An Analysis of Participants' Experiences from the First International MOOC Offered at the University of Oslo - Ammar Bahadur Singh; Anders I. Mørch (Universitetsforlaget, 2018)
Abstract This paper explores pedagogical practices and participants' engagement in learning activities during the first international Massive Open Online Course (MOOC) offered by the University of Oslo through the FutureLearn platform in 2015. The data were collected using pre- and post-course surveys and participant observations. We used the acquisition and participation metaphors of learning proposed by Sfard (1998) as a conceptual framework to inform our analyses and discussions. The data indicated that new pedagogical practices are in the making for online learning, involving elements of existing practices and radically new ones. The instructors had sole authority in developing and curating course contents, thus following the acquisition metaphor of teaching and learning. In addition, the data indicated that, overall, the learners had a positive experience of learning by participating in the MOOC. The learners engaged in online discussion forums, interacting asynchronously with fellow learners and mentors. The discussion forums promoted knowledge sharing and collaborative learning activities among diverse groups (joiners, surveyors, and social learners). The apparent contradiction between teaching according to the acquisition metaphor and the learners' preferences for the participation metaphor was resolved by some of the learners through self-organised scaffolding. The teachers did not interact enough with the learners and so, to compensate, some learners took on facilitating roles. We discuss our findings in terms of the related work and contemporary trends in online learning and higher education research, including learning analytics, formative assessment, personalization, collaboration support, and lifelong learning.